2018
DOI: 10.11606/1807-5509201700020345
|View full text |Cite
|
Sign up to set email alerts
|

Influência da gordura corporal no desempenho do salto com contramovimento em judocas de diferentes categorias de peso

Abstract: Rev Bras Educ Fís Esporte, (São Paulo) 2017 Abr-Jun; 31(2):345-53 • 345Influência da gordura corporal no desempenho do salto IntroduçãoInfluência da gordura corporal no desempenho do salto com contramovimento em judocas de diferentes categorias de peso ResumoEste estudo teve como objetivo verificar a influência da gordura corporal nos parâmetros cinéticos do salto vertical em judocas de diferentes categorias. Participaram deste estudo 48 judocas do sexo masculino agrupados por categorias: 55-60 kg/60-66 kg (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…On the contrary, the assessment of adiposity, often calculated as a physical body fat percentage, is a very important factor since excessive fat levels can be recognized as 'dead weight' and considered not useful when the body opposes gravity forces in movements such as running, pulling, jumping, etc. [7,[11][12][13][14]. Thus, in some cases, a self-implemented carbohydrate cycling program coupled with resistance training may be required to reduce body fat percentage and maintain muscle mass effectively in male athletes whose baseline means of body fat levels fluctuate between 9% and 15% [15].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the assessment of adiposity, often calculated as a physical body fat percentage, is a very important factor since excessive fat levels can be recognized as 'dead weight' and considered not useful when the body opposes gravity forces in movements such as running, pulling, jumping, etc. [7,[11][12][13][14]. Thus, in some cases, a self-implemented carbohydrate cycling program coupled with resistance training may be required to reduce body fat percentage and maintain muscle mass effectively in male athletes whose baseline means of body fat levels fluctuate between 9% and 15% [15].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the listed aspects, Athayde et al (2018), indicate that body fat negatively impacts countermovement jump performance in judo athletes. Kubo et al (2006), found that Japanese Olympic athletes or participants in Asian judo games had higher fat free mass (FFM) than athletes participating or not participating in university competitions.…”
Section: Introductionmentioning
confidence: 99%